2010
DOI: 10.1039/b926960f
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative double photoionization of CO2 molecules in the 36–49 eV energy range: angular and energy distribution of ion products

Abstract: Dissociative double photoionization of CO(2), producing CO(+) and O(+) ions, has been studied in the 36-49 eV energy range using synchrotron radiation and ion-ion coincidence imaging detection. At low energy, the reaction appears to occur by an indirect mechanism through the formation of CO(+) and an autoionizing state of the oxygen atom. In this energy range the reaction leads to an isotropic distribution of products with respect to the polarization vector of the light. When the photon energy increases, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 31 publications
5
46
0
Order By: Relevance
“…Correlation of this potential energy surface to the CO + (X 2 )/O + ( 4 S 0 ) fragmentation channel with a kinetic energy release (KER) of 6 eV was found in several studies using different approaches. 19,25,26 The anisotropy of ejected fragments in CO 2 has been studied in this energy range where Masuoka 16 and Alagia et al 25 reported anisotropic ion distributions for the primary dissociation channels. Eland et al 21 measured triply ionized states populated via core-electron excitation and found the lowest states at about 70 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of this potential energy surface to the CO + (X 2 )/O + ( 4 S 0 ) fragmentation channel with a kinetic energy release (KER) of 6 eV was found in several studies using different approaches. 19,25,26 The anisotropy of ejected fragments in CO 2 has been studied in this energy range where Masuoka 16 and Alagia et al 25 reported anisotropic ion distributions for the primary dissociation channels. Eland et al 21 measured triply ionized states populated via core-electron excitation and found the lowest states at about 70 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Details on the beamline and the end station have already been reported elsewhere [36], and the apparatus used for the experiment discussed here has also been described previously [37,38]. Therefore, only some features relevant to the present investigation are outlined here.…”
Section: Methodsmentioning
confidence: 99%
“…This device consists of a time-of-flight (TOF) spectrometer equipped with an ion position sensitive detector (stack of three micro-channel-plates with a multi-anode array arranged in 32 rows and 32 columns). It has been especially designed in order to properly measure the spatial momentum components of the dissociation ionic products [37]. Finally, by the analysis of distribution maps, the kinetic energy of the two products, released into the two ionic fragments, can be extracted.…”
Section: Methodsmentioning
confidence: 99%
“…They have been recorded by double photoionization experiments performed at the ELETTRA Synchrotron Light Laboratory (Trieste, Italy) using the angle-resolved photoemission spectroscopy (ARPES) end station of the gas phase beamline. Details about the beamline and the end station have been already reported elsewhere [27,28], and the apparatus used for the experiment discussed here has also been described previously [29][30][31]. Therefore, only some features relevant for the present investigation are outlined here.…”
Section: Methodsmentioning
confidence: 99%